Traffic-related air toxics and Parkinson's disease in California's Central Valley - Dayoon Kwon; Kanghong Shao; Karl O'Sharkey; Yu Yu; Jason Su; Jeff M. Bronstein; Beate Ritz (Science of The Total Environment, 2026)

Association between ambient air pollution and colorectal cancer risk: The Multiethnic Cohort Study - Ugonna Ihenacho; Chiuchen Tseng; Jun Wu; Scott Fruin; Timothy V. Larson; Salma Shariff-Marco; Loïc Le Marchand; Daniel O. Stram; Brian Z. Huang; Lynne R. Wilkens; Christopher A. Haiman; Beate Ritz; et al. (Environmental Research, 2026)

Maternal residential proximity to oil and gas development in California and the risk of childhood cancer - Yixin Chen; Lara J. Cushing; Shiwen Li; Myles Cockburn; Zuo-feng Zhang; Beate R. Ritz; Julia E. Heck (International Journal of Hygiene and Environmental Health, 2026)

Association of prenatal exposure to criteria air pollutants and traffic-related air toxics with adverse birth outcomes: A population-based cohort study in California (1990–2021) - Sanjali Mitra; Karl O'Sharkey; Seung-a Paik; Laura Thompson; Jason Su; Myles Cockburn; Roch A. Nianogo; Beate Ritz (Environmental Research, 2026)

Maternal occupational physical activity during pregnancy and childhood cancers in Denmark 1968–2013 - Xiwen Huang; Garikayi Chemhaka; Johnni Hansen; Chuanjie Deng; Niklas Krause; Beate Ritz; Julia E. Heck (International Archives of Occupational and Environmental Health, 2026)

Air toxics and late-life dementia and cognitive impairment in Mexican Americans - Yu Yu; Jason Su; Sanjali Mitra; Yufan Gong; Shiwen Li; Yuyuan Lin; Karl O'Sharkey; Kimberly C. Paul; Beate Ritz (Environmental Research, 2025)

Prenatal pesticide exposure and neuroblastoma – A statewide case-control study in California - Darcy Van Deventer; Beate Ritz; Myles Cockburn; Julia E. Heck (Environmental Research, 2025)

Agricultural copper pesticide exposure and DNA methylation in Central Valley of California residents with and without Parkinson's disease - Yufan Gong; Yu Yu; Keren Zhang; Irish Pearl Cambronero Del Rosario; Myles Cockburn; Laura K. Thompson; Adrienne M. Keener; Jeff Bronstein; Beate R. Ritz; Kimberly C. Paul (Environmental Research, 2025)

Challenges in studying air pollution to neurodegenerative diseases - Dayoon Kwon; Kimberly C. Paul; Karl O'Sharkey; Seung-A Paik; Yu Yu; Jeff M. Bronstein; Beate Ritz (Environmental Research, 2025)

Diet, polycyclic aromatic hydrocarbons, and oxidative stress biomarkers in pregnancy: A Los Angeles pregnancy cohort - Kasey E. Yu; Sanjali Mitra; Qi Meng; Irish DelRosario; Sherin U. Devaskar; Carla Janzen; Peggy S. Sullivan; Liwei Chen; Michael Jerrett; Beate Ritz (Environmental Research, 2025)

DNA methylation biomarkers for cumulative lead exposures and cognitive impairment - Kanghong Shao; Yu Yu; Beate Ritz; Kimberly C. Paul (Environmental Research, 2025)

Contributions of neighborhood physical and social environments to racial and ethnic disparities in birth outcomes in California: A mediation analysis - Shiwen Li; Lara J. Cushing; Roch A. Nianogo; Jonathan Liu; Rachel Connolly; Yu Yu; Michael Jerrett; Beate Ritz (Environmental Research, 2024)

Roadway construction as a natural experiment to examine air pollution impacts on infant health - Elaine Hill; Max Harleman; Lena Harris; Grace Sventek; Beate Ritz; Erin J. Campbell; Mary Willis; Perry Hystad (Environmental Research, 2024)

Effects of hypertension and use of antihypertensive drugs in pregnancy on the risks of childhood cancers in Taiwan - Helen T. Orimoloye; Ya-Hui Hu; Noah Federman; Beate Ritz; Onyebuchi A. Arah; Chung-Yi Li; Pei-Chen Lee; Julia E. Heck (Cancer Causes & Control, 2024)

Exposure to outdoor ambient air toxics and risk of breast cancer: The multiethnic cohort - Julia E. Heck; Di He; Sam E. Wing; Beate Ritz; Chandra D. Carey; Juan Yang; Daniel O. Stram; Loïc Le Marchand; Sungshim Lani Park; Iona Cheng; Anna H. Wu (International Journal of Hygiene and Environmental Health, 2024)

Cost-effectiveness analysis of insecticide ban aimed at preventing Parkinson's disease in Central California - Shiwen Li; Roch A. Nianogo; Yuyuan Lin; Hanwen Wang; Yu Yu; Kimberly C. Paul; Beate Ritz (Science of The Total Environment, 2024)

Neonatal per- and polyfluoroalkyl substance exposure in relation to retinoblastoma - Yixin Chen; Kimberly C. Paul; Douglas I. Walker; Dean P. Jones; Xuexia Wang; Beate R. Ritz; Julia E. Heck (Environmental Research, 2024)

Traffic-related air pollution and Parkinson's disease in central California - Dayoon Kwon; Kimberly C. Paul; Yu Yu; Keren Zhang; Aline D. Folle; Jun Wu; Jeff M. Bronstein; Beate Ritz (Environmental Research, 2024)

Preeclampsia, antihypertensive medication use in pregnancy and risk of childhood cancer in offspring - Lexie Askins; Helen T. Orimoloye; Chuanjie Deng; Johnni Hansen; Jorn Olsen; Beate Ritz; Carla Janzen; Julia E. Heck (Cancer Causes & Control, 2024)
Purpose Preeclampsia is a serious pregnancy complication that presents a significant risk to both the mother and the fetus. Preeclampsia and medications associated with its treatment are potentially linked to increased childhood cancer risk. Therefore, we examined the association between preeclampsia, antihypertensive medications, and childhood cancer in offspring. Methods Cases (n = 6,420) and controls (n = 160,484) were obtained from Danish national registries. We performed conditional logistic regression analyses to estimate the association between preeclampsia and childhood cancer risk, and examined the effects of antihypertensive medication use in pregnancy in relation to childhood cancer risk in the offspring with adjustment for relevant covariates. Results We observed an increased risk of acute lymphoblastic leukemia (ALL) among those whose mothers had preeclampsia (OR = 1.36, 95% CI 1.03, 1.79), especially for severe preeclampsia (OR = 2.36, 95% CI 1.37, 4.08). We also estimated an increased cancer risk in children born to mothers who were prescribed diuretics during pregnancy [OR = 2.09, 95% confidence interval (CI) 1.39, 3.14]. Intake of other antihypertensive medications was not associated with childhood cancer (OR = 0.78, 95% CI 0.50, 1.23). Among women who did not take diuretics in pregnancy, preeclampsia was associated with neuroblastoma (OR = 2.22, 95% CI 1.08, 4.55). Conclusion Our findings suggested an increased risk for certain types of cancer in the offspring of mothers with preeclampsia and an increased risk of cancer with diuretic intake during pregnancy.

Correction to: Higher testosterone and testosterone/estradiol ratio in men are associated with decreased Pheno‑/GrimAge and DNA‑methylation based PAI1 - Cynthia D. J. Kusters; Kimberly C. Paul; Ake T. Lu; Luigi Ferrucci; Beate R. Ritz; Alexandra M. Binder; Steve Horvath (GeroScience, 2023)

Exposure to per- and polyfluoroalkyl substances in early pregnancy and risk of cerebral palsy in children - Andreas Vilhelmsson; Lars Rylander; Anna Jöud; Christian H. Lindh; Kristina Mattsson; Zeyan Liew; Pengfei Guo; Beate Ritz; Karin Källén; Jesse D. Thacher (Science of The Total Environment, 2023)

Changes in traffic congestion and air pollution due to major roadway infrastructure improvements in Texas - Max Harleman; Lena Harris; Mary D. Willis; Beate Ritz; Perry Hystad; Elaine L. Hill (Science of The Total Environment, 2023)

Particulate matter, traffic-related air pollutants, and circulating C-reactive protein levels: The Multiethnic Cohort Study - Meera Sangaramoorthy; Juan Yang; Chiuchen Tseng; Jun Wu; Beate Ritz; Timothy V. Larson; Scott Fruin; Daniel O. Stram; Sung-shim Lani Park; Adrian A. Franke; Lynne R. Wilkens; Jonathan M. Samet; et al. (Environmental Pollution, 2023)

Letter to the editor - Julia E. Heck; Beate Ritz; Myles Cockburn; Shiraya Thompson (International Journal of Hygiene and Environmental Health, 2023)

Pan-primate studies of age and sex - Steve Horvath; Amin Haghani; Joseph A. Zoller; Ake T. Lu; Jason Ernst; Matteo Pellegrini; Anna J. Jasinska; Julie A. Mattison; Adam B. Salmon; Ken Raj; Markus Horvath; Kimberly C. Paul; et al. (GeroScience, 2023)
Age and sex have a profound effect on cytosine methylation levels in humans and many other species. Here we analyzed DNA methylation profiles of 2400 tissues derived from 37 primate species including 11 haplorhine species (baboons, marmosets, vervets, rhesus macaque, chimpanzees, gorillas, orangutan, humans) and 26 strepsirrhine species (suborders Lemuriformes and Lorisiformes). From these we present here, pan-primate epigenetic clocks which are highly accurate for all primates including humans (age correlation R = 0.98). We also carried out in-depth analysis of baboon DNA methylation profiles and generated five epigenetic clocks for baboons (Olive-yellow baboon hybrid), one of which, the pan-tissue epigenetic clock, was trained on seven tissue types (fetal cerebral cortex, adult cerebral cortex, cerebellum, adipose, heart, liver, and skeletal muscle) with ages ranging from late fetal life to 22.8 years of age. Using the primate data, we characterize the effect of age and sex on individual cytosines in highly conserved regions. We identify 11 sex-related CpGs on autosomes near genes ( POU3F2, CDYL, MYCL, FBXL4, ZC3H10, ZXDC, RRAS, FAM217A, RBM39, GRIA2, UHRF2 ). Low overlap can be observed between age- and sex-related CpGs. Overall, this study advances our understanding of conserved age- and sex-related epigenetic changes in primates, and provides biomarkers of aging for all primates.

Higher testosterone and testosterone/estradiol ratio in men are associated with decreased Pheno-/GrimAge and DNA-methylation based PAI1 - Cynthia D. J. Kusters; Kimberly C. Paul; Ake T. Lu; Luigi Ferruci; Beate R. Ritz; Alexandra M. Binder; Steve Horvath (GeroScience, 2023)
Sex hormones are hypothesized to drive sex-specific health disparities. Here, we study the association between sex steroid hormones and DNA methylation-based (DNAm) biomarkers of age and mortality risk including Pheno Age Acceleration (AA), Grim AA, and DNAm-based estimators of Plasminogen Activator Inhibitor 1 (PAI1), and leptin concentrations. We pooled data from three population-based cohorts, the Framingham Heart Study Offspring Cohort, the Baltimore Longitudinal Study of Aging, and the InCHIANTI Study, including 1,062 postmenopausal women without hormone therapy and 1,612 men of European descent. Sex-stratified analyses using a linear mixed regression were performed, with a Benjamini-Hochberg (BH) adjustment for multiple testing. Sex Hormone Binding Globulin (SHBG) was associated with a decrease in DNAm PAI1 among men (per 1 standard deviation (SD): -478 pg/mL; 95%CI: -614 to -343; P:1e-11; BH-P: 1e-10), and women (-434 pg/mL; 95%CI: -589 to -279; P:1e-7; BH-P:2e-6). The testosterone/estradiol (TE) ratio was associated with a decrease in Pheno AA (-0.41 years; 95%CI: -0.70 to -0.12; P:0.01; BH-P: 0.04), and DNAm PAI1 (-351 pg/mL; 95%CI: -486 to -217; P:4e-7; BH-P:3e-6) among men. In men, testosterone was associated with a decrease in DNAm PAI1 (-481 pg/mL; 95%CI: -613 to -349; P:2e-12; BH-P:6e-11). SHBG was associated with lower DNAm PAI1 among men and women. Higher testosterone and testosterone/estradiol ratio were associated with lower DNAm PAI and a younger epigenetic age in men. A decrease in DNAm PAI1 is associated with lower mortality and morbidity risk indicating a potential protective effect of testosterone on lifespan and conceivably cardiovascular health via DNAm PAI1. Graphical Abstract

Proximity to residential and workplace pesticides application and the risk of progression of Parkinson's diseases in Central California - Shiwen Li; Beate Ritz; Yufan Gong; Myles Cockburn; Aline Duarte Folle; Irish Del Rosario; Yu Yu; Keren Zhang; Emily Castro; Adrienne M. Keener; Jeff Bronstein; Kimberly C. Paul (Science of The Total Environment, 2023)

Parental occupation and childhood germ cell tumors: a case–control study in Denmark, 1968–2016 - Clinton Hall; Johnni Hansen; Jørn Olsen; Di He; Ondine S. von Ehrenstein; Beate Ritz; Julia E. Heck (Cancer Causes & Control, 2021)
Purpose To examine associations between parental occupation and childhood germ cell tumors (GCTs) in offspring while distinguishing by common histologic subtype (i.e., yolk sac tumor and teratoma). Methods This population-based case–control study included childhood GCT cases in Denmark diagnosed 1968–2015 (< 16 years old at diagnosis) and sex and birth year-matched controls. Demographic information and parental employment histories were obtained from Danish registries. Parental occupation was assessed by industry; job-exposure matrices were used to examine specific occupational exposures (i.e., potentially carcinogenic organic solvents and social contact). Conditional multivariable logistic regression models were used to estimate odds ratios (OR) and 95% confidence intervals (CIs). Results Overall, 178 childhood GCT cases (50 yolk sac tumors; 65 teratomas) and 4,355 controls were included for analysis. Maternal employment in education during pregnancy was associated with offspring GCTs (OR 2.45, 95% CI 1.23–4.90), especially yolk sac tumors (OR 5.27, 95% CI 1.94–14.28). High levels of both maternal and paternal occupational social contact were also associated with offspring yolk sac tumors across all exposure periods (ORs 2.30–4.63). No signals were observed for paternal occupational solvent exposure, while imprecise associations were estimated for maternal exposure (e.g., dichloromethane exposure during pregnancy, OR 1.51, 95% CI 0.77–2.95). Conclusion Our findings suggest that parental occupation is associated with offspring GCTs, with most consistent evidence supporting an association between maternal employment in education or other high social contact jobs and offspring yolk sac tumors.

Correction to: Air Pollution and Adverse Pregnancy and Birth Outcomes: Mediation Analysis Using Metabolomic Profiles - Kosuke Inoue; Qi Yan; Onyebuchi A. Arah; Kimberly Paul; Douglas I. Walker; Dean P. Jones; Beate Ritz (Current Environmental Health Reports, 2020)

Air Pollution and Adverse Pregnancy and Birth Outcomes: Mediation Analysis Using Metabolomic Profiles - Kosuke Inoue; Qi Yan; Onyebuchi A. Arah; Kimberly Paul; Douglas I. Walker; Dean P. Jones; Beate Ritz (Current Environmental Health Reports, 2020)

Occupational livestock or animal dust exposure and offspring cancer risk in Denmark, 1968–2016 - Clinton Hall; Johnni Hansen; Ondine S. von Ehrenstein; Di He; Jørn Olsen; Beate Ritz; Julia E. Heck (International Archives of Occupational and Environmental Health, 2020)

Type 2 Diabetes Mellitus and Alzheimer’s Disease: Overlapping Biologic Mechanisms and Environmental Risk Factors - Kimberly C. Paul; Michael Jerrett; Beate Ritz (Current Environmental Health Reports, 2018)

Maternal pre-pregnancy and gestational diabetes, obesity, gestational weight gain, and risk of cancer in young children: a population-based study in California - Zuelma A. Contreras; Beate Ritz; Jasveer Virk; Myles Cockburn; Julia E. Heck (Cancer Causes & Control, 2016)

Of Pesticides and Men: a California Story of Genes and Environment in Parkinson’s Disease - Beate R. Ritz; Kimberly C. Paul; Jeff M. Bronstein (Current Environmental Health Reports, 2016)

Maternal diet during pregnancy and unilateral retinoblastoma - Christina Lombardi; Arupa Ganguly; Greta R. Bunin; Saeedeh Azary; Vivian Alfonso; Beate Ritz; Julia E. Heck (Cancer Causes & Control, 2015)

Exposure to particulate matter and adverse birth outcomes: a comprehensive review and meta-analysis - Amir Sapkota; Adam P. Chelikowsky; Keeve E. Nachman; Aaron J. Cohen; Beate Ritz (Air Quality, Atmosphere & Health, 2012)

Perinatal characteristics and retinoblastoma - Julia E. Heck; Christina A. Lombardi; Travis J. Meyers; Myles Cockburn; Michelle Wilhelm; Beate Ritz (Cancer Causes & Control, 2012)

Nested case–control study of occupational physical activity and prostate cancer among workers using a job exposure matrix - Anusha Krishnadasan; Nola Kennedy; Yingxu Zhao; Hal Morgenstern; Beate Ritz (Cancer Causes & Control, 2008)

Circulating Melatonin Levels: Possible Link Between Parkinson’s Disease and Cancer Risk? - Eva Schernhammer; Honglei Chen; Beate Ritz (Cancer Causes & Control, 2006)